Persepsi Para Mubaligh Terhadap Wacana Kontroversi Standardisasi Khatib dan Sertifikasi Mubaligh - Arsam Arsam (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2017)
Today, there is a discourse of controversy that disturbs society, especially the muballigh and khatib related to the discourse of standardization of preachers and muballigh certification. Controversy on the discourse of standardization of preachers and certification of muballigh occurred between the government and some circles including the leaders and the mosque or mosque official. On the one hand, the government states that certification of muballigh and standardization of khatib is very necessary and important to do. While on the other hand a number of figures refuse the certification of muballigh and standardization of preacher. From the above background can be formulated “How is the perception of the Muballigh in Banyumas against the controversy of khatib standardization and certification of muballigh? “How are the hopes of the muballigh in Banyumas related to the controversy of khatib standardization and muballigh certification? The type of research used in this study is a qualitative research that is a research procedure that produces deksriptif data in the form of written or oral words of the people and behavior that can be observed. The research method used in this research is descriptive qualitative method. The method of data analysis used in this study is the method of data analysis by Mile and Huberman. The results of this study include: a) Views that support adanyba khatib standardization and certification of preachers with records starting with the training and get a salary from the government. b). Views that reject the standardization of preachers and certification preachers. Both terms are deemed inaccurate and more precisely is the formation of forums silaturrahim between preachers and preachers in which is filled with sharing sharing about the problems of preachers and the public. c). Alternative view is to provide a new alternative by empowering the existing religious counselors within the ministry of religion to accompany the preachers or form forum silaturrohim between preachers and preachers. While the expectations of the preachers to the controversy of standardization of preachers and certification of preachers are as follows: a). For preachers to improve their competence so that the goal to give the enlightenment of reason and conscience can be realized. b). For preachers in lectures not to vilify other groups, enlarge khilafiyah and not anti Pancasila and constitution 45.